Nanofibrils of food‐grade proteins: Formation mechanism, delivery systems, and application evaluation. Issue 6 (6th October 2022) - An, Di; Ban, Qingfeng; Du, Hengjun; Wang, Qi; Teng, Fei; Li, Liang; Xiao, Hang
Abstract: Due to the high aspect ratio, appealing mechanical characteristics, and various adjustable functional groups on the surface proteins, food‐grade protein nanofibrils have attracted great research interest in the field of food science. Fibrillation, known as a process of peptide self‐assembly, is recognized as a common attribute for food‐grade proteins. Converting food‐grade proteins into nanofibrils is a promising strategy to broaden their functionality and applications, such as improvement of the properties of gelling and emulsifying, especially for constructing various delivery systems for bioactive compounds. Protein source and processing conditions have a great impact on the size, structure, and morphology of nanofibrils, resulting in extreme differences in functionality. With this feature, it is possible to engineer nanofibrils into four different delivery systems, including gels, microcapsules, emulsions, and complexes. Construction of nanofibril‐based gels via multiple cross‐linking methods can endow gels with special network structures to efficiently capture bioactive compounds and extra mechanical behavior. The adsorption behavior of nanofibrils at the interface is highly complex due to the influence of several intrinsic factors, which makes it challenging to form stabilized nanofibril‐based emulsion systems. Based on electrostatic interactions, microcapsules and complexes prepared using nanofibrils and polysaccharides have combined functional properties, resulting in adjustable release behavior and higher encapsulation efficiency. The bioactive compounds delivery system based on nanofibrils is a potential solution to enhance their absorption in the gastrointestinal tract, improve their bioavailability, and deliver them to target organs. Although food‐grade protein nanofibrils show unknown toxicity to humans, further research can contribute to broadening the application of nanofibrils in delivery systems.